Konsep Akulturasi Budaya Lokal Dalam Tafsir Qur’an Telaah Mufasir Kawasan Asia Tenggara - Amiruddin, Amiruddin; Jabbar, Luqman Abdul (Indo Publishing, 2026)
Islam as a universal religion has emerged and developed within diverse social and cultural contexts. In Southeast Asia, the process of Islamization occurred through peaceful and dialogical mechanisms of cultural acculturation. This phenomenon has significantly influenced the patterns of Qur’anic interpretation that developed in the region. This article aims to examine the concept of local cultural acculturation in Qur’anic exegesis by analyzing the thoughts of Southeast Asian mufassirs. This study employs a qualitative method with a library research approach, along with descriptive-analytical analysis of representative tafsir works from Southeast Asia. The findings indicate that Southeast Asian mufassirs integrate local cultural values into Qur’anic interpretation as long as they do not contradict the fundamental principles of Islam. Such acculturation is reflected in the language of interpretation, socio-cultural approaches, and an emphasis on values of moderation, tolerance, and social harmony. Thus, Qur’anic exegesis in Southeast Asia represents a contextual interpretive model that reinforces an inclusive image of Islam as rahmatan lil ‘alamin.